A MINI-REVIEW OF RECENT STUDIES ON LEAD AND LEAD-FREE PEROVSKITE MATERIALS FOR SOLAR CELLS APPLICATION AND THEIR ISSUES (Jurnal Teknologi (Sciences & Engineering), 2022)
Perovskite is gaining popularity in solar cell technologies and optoelectronics that rely on lead-based material. Perovskite solar cell (PSC) technologies are viewed as promising forthcoming innovations for their proficiency and monetary of the thin film due to high demand in the technology market. Lead-free perovskite material has become a viable alternative to lead-based perovskite, which has dominated the solar cell market for many years, due to toxicity and stability difficulties that have plagued lead-based solar cells. The large-scale commercial manufacture of lead-free halide perovskites solar cells can be expanded and its benefits in the solar field could be enhanced. Compared with lead-based perovskite, the lead-free perovskite material could also achieve a high-power conversion efficiency (PCE) indicating good solar cell performance. This review studied the perovskite materials, challenge of lead perovskite solar cell commercialization and summarizes recent research work regarding the perovskite solar cell. Moreover, this review forecast the future of perovskite solar cells in parallel with the Third Generation of Solar Cells.